2022
DOI: 10.1007/s10758-022-09599-6
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mobile App Use for Teaching and Research in Higher Education

Abstract: The exponential growth in the use of digital technologies and the availability of mobile software applications (apps) has been well documented over the past decade. Literature on the integration of mobile technology into higher education reveals an increasing focus on how mobile devices are used within the classroom environment, both physical and online, rather than on how mobile applications may be used for either teaching or the research process. Our study surveyed staff and higher degree research students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The study also found that academic librarians are now using WhatsApp to communicate with users. As confirmed by Chaputula et al (2020, p. 717), Hinze et al (2022, p. 2), Mogale and Bopape (2023, p. 4) and Tsang and Chiu (2022, p. 5), this is now a trend, that has been adopted in many libraries across the globe. Consequently, it can be used as an indicator that users are enjoying accessing library services via mobile technology gadgets such as tablets, smartphones and laptops.…”
Section: Findings and Discussionmentioning
confidence: 72%
“…The study also found that academic librarians are now using WhatsApp to communicate with users. As confirmed by Chaputula et al (2020, p. 717), Hinze et al (2022, p. 2), Mogale and Bopape (2023, p. 4) and Tsang and Chiu (2022, p. 5), this is now a trend, that has been adopted in many libraries across the globe. Consequently, it can be used as an indicator that users are enjoying accessing library services via mobile technology gadgets such as tablets, smartphones and laptops.…”
Section: Findings and Discussionmentioning
confidence: 72%
“…Researchers started designing mobile applications. which is the application system that students will later use for the learning process (Jayatilleke et al, 2018;Oliveira et al, 2021;Hinze et al, 2023). The stages carried out are creating the application user interface, designing the application system, and then carrying out maintenance on the application system.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Some Ukrainian researchers have addressed the issue of using modern innovative technological capabilities in the course of learning a foreign language to increase the pace and quality of the educational process. Scientists emphasize that compared with traditional methodologies, mobile learning tools have significant advantages because they stimulate independent study of materials and self-development, individualize the educational process, and increase the level of motivation of education seekers (Gorbatiuk et al, 2019;Hinze et al, 2023;Mozharovska, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%